Managing emotions in university students in times of confinement: An intervention proposal from a classroom project - Acuña-Rodríguez, Mónica Patricia; Gómez-López, Yeferson; Umaña-Ibáñez, Samir Francisco; Ramírez-Ordoñez, María Jesús; Acuña-Rodríguez, Janiris Del Carmen (Boletín de Innovación, Logística y Operaciones, 2021)
The constant transformations of the system have allowed the subjects to face various situations that reveal behaviors resulting from the appearance of positive and negative emotions.The present study aims to describe an intervention proposal for the management of emotions in students university students in times of confinement from a classroom project. The research developed was qualitative, descriptive in scope, from the systematization of experiences. The implemented technique was the virtual annotation record, supported by the teams tools. The participating population were the students of the emotion and motivation subject of the face-to-face and remote group of the period 2021-1. The results indicate that young university students determine that covid 19 has been a virus that has impacted their mental health, especially with what they fearfully call loneliness, the fact of being locked up at home all the time, not just the impossibility of enjoying the activities with which they felt full, but also have led them to overload themselves with family problems that in normal situations they "avoid". Among the conclusions, it is highlighted that Emotions are subjective, appear quickly, and allow individuals to act in a particular way, they function as an indicator to say how the individual is doing with survival, that is why there are different elements that intervene at the time of experiencing emotions and has to do with content, feelings, body stimulation, sense of intention and expressions.